Regulation of the Transferrin Receptor Recycling in Hepatitis C Virus-Replicating Cells - Haberger, Vanessa; Elgner, Fabian; Roos, Jessica; Bender, Daniela; Hildt, Eberhard (Frontiers in Cell and Developmental Biology, 2020)
After binding of its ligand transferrin, the transferrin receptor (TfR) is internalized via early endosomes. Ligand and receptor can be recycled. α-taxilin was identified as an essential factor for TfR recycling. Apart from its role for iron uptake TfR is a coreceptor for HCV infection. In HCV replicating cells the amount of -taxilin is decreased. This study aims to investigate the effect of decreased α-taxilin levels in HCV-replicating cells on recycling of TfR, its amount on the cell surface, on iron uptake and the impact of a disturbed TfR recycling on HCV superinfection exclusion. TfR amount and localization were determined by CLSM and surface biotinylation. α taxilin expression was modulated by CRISPR-Cas9 knockout, siRNA and stable or transient overexpression. For analysis of HCV superinfection fluorophor-tagged reporter viruses were used. The amount of α-taxilin is decreased in HCV-infected cells. In accordance to this, the protein amount of TfR is significant lower in HCV-positve cells as compared to the control, while TfR- expression is not affected. Due to the impaired recycling, internalized TfR is degraded by the endosomal/lysosomal system. The significant lower number of TfR molecules on the cell surface is reflected by reduced transferrin binding / internalization and strong reduction of intracellular iron level. Overexpression of α-taxilin in HCV replicating cells rescues TfR recycling, augments TfR on the cell surface and restores transferrin binding. The block of superinfection in HCV replicating cells could be overcome by overexpression of α-taxilin. Taken together, the diminished level of α-taxilin in HCV-replicating cells prevents recycling of TfR leading to decreased transferrin binding and iron uptake. Disappearance of TfR from the cell surface could be a factor contributing to the exclusion of superinfection by HCV.